Controlled Switching of the Number of Skyrmions in a Magnetic Nanodot by Electric Fields. Issue 11 (4th February 2022) - Hou, Zhipeng; Wang, Yadong; Lan, Xiaoming; Li, Sai; Wan, Xuejin; Meng, Fei; Hu, Yangfan; Fan, Zhen; Feng, Chun; Qin, Minghui; Zeng, Min; Zhang, Xichao; et al.
Abstract: Magnetic skyrmions are topological swirling spin configurations that hold promise for building future magnetic memories and logic circuits. Skyrmionic devices typically rely on the electrical manipulation of a single skyrmion, but controllably manipulating a group of skyrmions can lead to more compact and memory‐efficient devices. Here, an electric‐field‐driven cascading transition of skyrmion clusters in a nanostructured ferromagnetic/ferroelectric multiferroic heterostructure is reported, which allows a continuous multilevel transition of the number of skyrmions in a one‐by‐one manner. Most notably, the transition is non‐volatile and reversible, which is crucial for multi‐bit memory applications. Combined experiments and theoretical simulations reveal that the switching of skyrmion clusters is induced by the strain‐mediated modification of both the interfacial Dzyaloshinskii–Moriya interaction and effective uniaxial anisotropy. The results not only open up a new direction for constructing low‐power‐consuming, non‐volatile, and multi‐bit skyrmionic devices, but also offer valuable insights into the fundamental physics underlying the voltage manipulation of skyrmion clusters. Abstract : An electric‐field‐driven cascading transition of skyrmion clusters in nanostructured ferromagnetic/ferroelectric multiferroic heterostructure is realized, which allows a continuous multilevel transition of the number of skyrmions in a one‐by‐one manner. Most notably, the transition is non‐volatile and reversible. The results open up a new direction for constructing low‐power‐consuming, non‐volatile, and multi‐bit skyrmionic devices.